CORRELATION OF INTERNAL COMMUNICATION WITH EMOTIONAL INTELLIGENCE IN PROJECT TEAMS IN ORGANIZATION “X” - Zakrizevska Belogrudova, Maija; Antonova, Lasma (SOCIETY. INTEGRATION. EDUCATION. Proceedings of the International Scientific Conference, 2021)
Nowadays, due to the fierce market competition, the volume, complexity and requirements of projects are increasing, resulting in intensive communication in project teams. Statistics show that one out of five projects is unsuccessful due to ineffective communication. The role of emotional intelligence in project management has been little studied, but it is believed that promoting emotional intelligence can improve internal communication within the project team. The aim of the research was to study the emotional intelligence and internal communication correlation of project managers and team members in organization “X” in order to develop proposals for the management of organization “X” for promoting emotional intelligence and improving internal communication. The emotional intelligence of project managers and team members was measured by using a survey of emotional and social intelligence competencies. Internal communication in project teams was assessed by using a survey based on aspects of effective internal communication within the project team. The results of the study showed that there is a statistically significant and strong correlation between emotional intelligence of project managers and team members and internal communication in project teams. “Self-management” and “social awareness” or the ability to adapt to other people were identified as the most important competencies of emotional intelligence which are required in order to improve internal communication.